Marshall McLuhan's mosaic : probing the literary origins of media studies - Lamberti, Elena (University of Toronto Press, 2012)
"One hundred years after Marshall McLuhan's birth, Elena Lamberti explores a fundamental, yet neglected aspect of his work: the solid humanistic roots of his original 'mosaic' form of writing. In this investigation of how his famous communication theories were influenced by literature and the arts, Lamberti proposes a new approach to McLuhan's thought.